OPTIMALISASI EMERGENCY SYSTEM TOWER SEBAGAI ASSURANCE PERSONEL ATC DI BANDAR UDARA INTERNASIONAL SULTAN AJI MUHAMMAD SULAIMAN SEPINGGAN BALIKPAPAN - Rosyidha Hayyu Hibatullah; Dewi Ratnasari; Putu Agus Valguna (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The emergency system tower has an important role in maintaining the safety of ATC personnel while inside the tower. The existence of an emergency system will make it easier for ATC to evacuate themselves when in a dangerous situation (emergency) which requires less time. The problem reviewed in this final project is the incomplete emergency system for ATC personnel in the tower building at Sultan Aji Muhammad Sulaiman Sepinggan International Airport, Balikpapan. The purpose of writing is to provide insight and reference material for further researchers. As well as knowing the resolution of problems related to the incomplete emergency system for ATC personnel in evacuating themselves from the tower at Sultan Aji Muhammad Sulaiman Sepinggan International Airport, Balikpapan. In this study, the data collection methods that the author uses are observation, documentation and literature study. This type of research uses a qualitative descriptive method. The author hopes that this paper can be used as a consideration for maintenance and addition of supporting facilities such as equipment that can support the creation of safety and security Emergency Exit in the tower building of Perum LPPNPI Balikpapan Branch